William Whitaker interviewed by Ana Tostões - Tostões, Ana (Docomomo Journal, 2018)
In February 2018, Ana Tostões interviewed William Whitaker, curator and collections manager of the Architectural Archives of the University of Pennsylvania School of Design, where the Louis I. Kahn Collection is hosted, in order to debate the importance of documentation for the preservation of Kahn’s legacy. William Whitaker was curatorial consultant of the exhibition Louis Kahn: The Power of Architecture (Vitra Design Museum, 2012) and is the co-author of The Houses of Louis I. Kahn (with George Marcus, 2013), the first comprehensive publication on the architect’s house designs. The management of the Louis I. Kahn Collection has been having a fundamental role, not only in the documentation and interpretation of Kahn’s life and work, but also in the success of the contemporary rehabilitation projects undertaken in his buildings.